Factors associated with SARS-CoV-2 SRAS cases in elderly people with cardiovascular disease (Research, Society and Development, 2022)
The present work aims to profile the cases of Severe Acute Respiratory Syndrome (SARS) caused by SARS-CoV-2 in elderly people with chronic cardiovascular diseases. It is an ecological and descriptive research, with a quantitative approach. Data recorded between January 6, 2020 and September 3, 2021, from the Coronavirus Panel, made available by the Ministry of Health, were used. The sample included 2,400 cases of SARS caused by SARS-CoV-2 in elderly people with chronic cardiovascular disease residing in Paraíba. Data were analyzed using the Rstudio software, where Pearson's chi-square test was used to verify the association between the variables under study. Of the total number of cases, the majority were female elderly (51.6%), aged up to 75 years (52.1%), brown (77%), with elementary school 1 cycle (35.4%) and residents of the urban area (91.1%). The most prominent signs and symptoms were: fever, cough, dyspnea, respiratory distress and O2 saturation < 92%. Of the total number of cases investigated, 54.5% died. In view of the above, it was observed that the elderly with cardiovascular disease pre-existing Covid-19 infection should be followed up with greater caution after the diagnosis of the infection, as they present a great risk of prognosis and unfavorable outcome. In addition, it is important to highlight that compliance with classic preventive measures, in particular vaccination, is of great need in order to reduce the spread of Covid-19.